Was Obama Elected by the Internet? Broadband Diffusion and Voters' Behavior in US Presidential Elections - Valentino Larcinese; Luke Miner (Center for Economic Studies and ifo Institute (CESifo), 2018)
What are the political consequences of the diffusion of broadband internet? We address this question by studying the 2008 US presidential election, the first political campaign where the internet played a key role. Drawing on data from the FEC and the FCC, we provide robust evidence that internet penetration in US counties is associated with an increase in turnout, an increase in campaign contributions to the Democrats and an increase in the share of Democratic vote. We then propose an IV strategy to deal with potential endogeneity concerns: we exploit geographic discontinuities along state borders with different right-of-way laws, which constitute the main determinant of the cost of building new infrastructure. IV estimates confirm a positive impact of broadband diffusion on turnout, while the pro-Democratic Party effect of the internet appears to be less robust.
Keywords: D72; L86; 330; internet diffusion; political economy of the media; United States elections; turnout; campaign contributions